IN VITRO SCREENING AND IDENTIFICATION OF ANTIOXIDANT ACTIVITIES OF ORANGE (CITRUS SINENSIS) PEEL EXTRACT IN DIFFERENT SOLVENTS - S. SWAPNA REKHA; M. BHASKAR (International Journal of Pharma and Bio Sciences, 2013)
Citrus plants are the rich source of secondary metabolites which includes alkaloids, steroids, tanins, flavonoids, phenols and polyphenols. Having the rich source of polyphenols and natural flavonoids draw attention to screen the phytochemical compounds and their beneficial activities from different solvents. The present investigation explore the in vitro antioxidant activity of orange (Citrus sinensis) peel extract from different solvents gives reliable information and best extraction procedures to screen the phytochemicals. Among the different solvent extracts methonolic extract exhibits the highest in vitro scavenging activity followed by other solvent extracts which includes Ethanolic, Hexane, Benzene, Ethyl acetate, and chloroform with IC50 values 65.44,120, 138.45, 151.34, 170.34, 185.35 with 55.6 % inhibitory concentration of ascorbic acid. The screening and scavenging activities of secondary metabolites form different solvents may improve the best extraction procedures and functional activities of beneficial compounds. In this regard to reach a conclusion that methonolic orange peel extract followed by ethonolic extract showed their high potential effectiveness as antioxidant activity when compared to the other solvent extracts.